Asymmetry of the leg stretcher force high-performance female and male juniors in sweep rowing - Mattes, K.; Wolff, S. (International Journal of Performance Analysis in Sport, 2019)
The geometry of sweep rowing causes an asymmetrical movement with uneven force distribution on both sides of the body. The aim of this study was to investigate the asymmetry of the stretcher force for junior women and men. Four rowing eight-crews (N = 32) completed a stroke rate test and a 2000 m race. The rowing angle, the handle force and the stretcher force for the inside (oarside) and outside (non oarside) leg were measured. In both sub-samples, the outside leg stretcher force was higher than the inside leg stretcher force. The women rowed with higher symmetry index of stretcher force (26.8 ± 19.7%) than the men (8.6 ± 15.9%). This asymmetry was reduced with increasing stroke rate but increased with physical fatigue in the course of the rowing race. The transmission to the oar via trunk and arms is associated with unequal loading of the pelvis and lumbar spine. Female and male sweep rowers with high asymmetry of the stretcher force should use appropriate strength and technique training to reduce the asymmetry and the risk of low back pain.